A narrative review of computational thinking in Compulsory Secondary Education - Óscar Marañón Marañón; Higinio González-García (Universidad de La Rioja, 2021)
The objective of this work was to know the benefits that computational thinking brings to education and the proposals for its application in Secondary Education in the different Spanish regions and other European countries. For this, a narrative review of the scientific literature has been carried out, extracting articles in both languages Spanish and English from the following databases: Dialnet, Scopus, Google Scholar, Researchgate and Microsoft Academic. Among the main results found, in many countries the current trend is to introduce it into the curriculum, as well as a series of skills, characteristics and attitudes associated with it, including abstraction, problem decomposition, algorithmic thinking, automation, debugging and generalization. Among the main benefits that computational thinking brings is the improvement of digital competence, development and strengthening of socio-emotional skills, skills related to language and communication, and empowerment of collective work. As a conclusion, it is important to highlight that most of the European countries have implemented or are in the process of implementing more actions to strengthen the use of computational thinking among students.